Professional health, occupational stress and occupational nursing performance (Research, Society and Development, 2022)
Objective: To examine scientific productions that address discussions on professional health, occupational stress, and occupational nursing, highlighting ways to improve professional health so that work practice is carried out more efficiently. Methods: This is an integrative literature review built from the search in the databases: Database in Nursing - Brazilian Bibliography (BDENF), Online System for Search and Analysis of Medical Literature (MEDLINE/PUBMED), Web of Science Cochrane Library (SCOPUS) and Latin American and Caribbean Literature in Health Sciences (LILACS). Descriptors were used according to the list of Descriptors in Health Sciences (DeCS): Occupational nursing, Occupational Health, and Professional Practice. The following were included: studies with free access, available online, complete, in English/Portuguese/Spanish, and published between the years 2017 to 2022. Results: There is a correlation between occupational stress and workers' health, where job satisfaction directly interferes with their well-being. Final considerations: Occupational nursing is very important for professional health, as it has an educator and care provider role.